Aztec multilatinas: characteristics and strategies of Mexican multinationals. Issue 1 (5th March 2018) - Huesca-Dorantes, Jose L.; Michailova, Snejina; Stringer, Christina
Abstract : Purpose: This paper provides an overview of the Aztec 13 – the top 13 multinational enterprises in Mexico. Different from research that groups countries and regions, the purpose of the paper is to deliver a nuanced picture of these multinationals in terms of their key characteristics and the strategies they follow when they internationalize. Design/methodology/approach: All data sources that have been identified and reviewed are documents, printed and electronic. The Aztec multilatinas were identified using Forbes Global 2000 (2017 ). Other data sources such as media texts, company annual reports, reports filed with the Mexican Stock Exchange and the US Securities and Exchange Commission, as well as investor presentations, were collected and analyzed. Data sources were published in English and Spanish. The analytic procedure adopted entailed identifying, selecting, making sense of and synthesizing the data contained in the documents. Findings: Aztec multilatinas have specific characteristics which, to a great extent, influence their internationalization strategies. Characteristics include the geographical location of their headquarters, their origin and history, their ownership structure and ties with families and government. These factors, combined, help to describe in greater nuance the internationalization strategies and activities of the Aztec 13. Such a detailed and focused description is a first necessary step for subsequent potential theorizing. Originality/value: This paper contributes to the vibrant scholarly conversation on multinational enterprises from less researched regions and countries. Latin America is such a region and Mexico is such a country. Focusing on a single country and its top 13 multinationals allow a comprehensive description and disciplined analysis, with no dangerous generalizations to large regions and even larger settings such as emerging markets multinationals and with no false claims for theorizing.